Composite mineral admixture, preparation method thereof and concrete

By modifying dolomite powder and using it in conjunction with other mineral blends, the problem of low dolomite powder activity is solved, significantly improving the strength and durability of concrete, and forming a denser hydration product network.

CN119661109AInactive Publication Date: 2025-03-21GUANGDONG HUANAN CONCRETE CO LTD

Patent Information

Application Number
CN202411843572.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-14
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Dolomite powder is less active in concrete, which limits its ability to fully utilize its potential effectiveness in concrete, making it difficult to maximize the strength, durability and working performance of concrete.

Method used

By blending dolomite powder with gypsum and calcium hydroxide and using surface modification technology, the volcanic ash activity and compatibility of dolomite powder are enhanced. Then, the modified dolomite powder is reasonably matched with nickel slag, metakaolin, and desulfurization ash to prepare a high-performance composite mineral blend.

Benefits of technology

It significantly improves the strength and durability of concrete, and the synergistic effect of modified dolomite powder and other mineral blends form a denser and stable hydration product network, improving the density and working performance of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005188517320000071
    Figure BDA0005188517320000071
  • Figure BDA0005188517320000081
    Figure BDA0005188517320000081
Patent Text Reader

Abstract

The invention relates to the technical field of concrete materials, and particularly discloses a composite mineral admixture, a preparation method thereof and concrete. The preparation method of the composite mineral admixture comprises the following steps: mixing and modifying dolomite powder, gypsum and calcium hydroxide to obtain pre-modified dolomite powder; then adding hexadecyl trimethyl ammonium chloride and octylphenol polyoxyethylene ether to obtain modified dolomite powder; and adding nickel slag, metakaolin, desulfurized fly ash and a grinding aid, and grinding to obtain the composite mineral admixture. The concrete prepared from the composite mineral admixture is excellent in compressive strength, shrinkage resistance, permeation resistance and the like, and the strength and durability of the concrete can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete materials, and in particular to a composite mineral admixture and a preparation method thereof, and concrete. Background Art

[0002] In recent years, with the growing demand for high-performance and environmentally friendly building materials, the research and application of composite mineral admixtures have received increasing attention. Traditional mineral admixtures such as fly ash play an important role in improving the performance of concrete due to its unique pozzolanic activity and fine aggregate effect. However, the limited and uneven distribution of fly ash resources, as well as its limited adaptability to specific engineering environments, have prompted researchers to look for more extensive, economical and efficient alternatives. In this context, dolomite powder, as a potential fly ash substitute, has gradually attracted the attention of the research community.

[0003] As a mineral that is widely present in nature, has abundant resources and is low in cost, dolomite is suitable for large-scale application. Studies have shown that refined dolomite powder also has a filling effect and a certain activity, and can synergize with other mineral admixtures to improve the comprehensive performance of concrete. However, despite its huge potential, dolomite powder faces a significant challenge when used directly as a mineral admixture: its own activity is relatively low, which limits its ability to fully exert its potential in concrete. The low activity of dolomite powder means that the speed and degree of its participation in cement hydration reactions are limited, making it difficult to maximize the strength, durability and workability of concrete. It is difficult to fully exert its potential by directly adding dolomite powder to concrete. Therefore, it is urgent to explore a technical means to stimulate the potential activity of dolomite powder, so that it can be better integrated into the concrete system, synergize with other admixtures, and jointly promote concrete performance to new heights. Summary of the invention

[0004] In order to improve the activity of dolomite powder, the present application provides a composite mineral admixture, a preparation method thereof, and concrete. The present application enhances the volcanic ash activity of dolomite powder by blending dolomite powder, gypsum, and calcium hydroxide, and supplemented by surface modification technology, and further improves the compatibility and synergistic effect of dolomite powder and other mineral admixtures. Furthermore, the present application reasonably combines modified dolomite powder with nickel slag, metakaolin, and desulfurization ash, and these mineral admixtures work synergistically to produce a high-performance composite mineral admixture, the application of which in concrete can significantly improve the strength and durability of concrete.

[0005] In the first aspect, the present application provides a method for preparing a composite mineral admixture using the following technical solution: A method for preparing a composite mineral admixture comprises the following steps: Step 1: Weigh 100 parts of dolomite powder, 20-30 parts of gypsum, and 10-15 parts of calcium hydroxide, mix them evenly, add 50-60 parts of water while stirring, dry after the reaction is completed, and grind to a specific surface area of ​​400-500m 2 / kg, and pre-modified dolomite powder was obtained; Step 2: Take pre-modified dolomite powder, spray the aqueous solution containing hexadecyl trimethyl ammonium chloride and octylphenol polyoxyethylene ether while stirring, mix well and then dry to obtain modified dolomite powder, wherein the addition amount of the hexadecyl trimethyl ammonium chloride is 1%-2% of the mass of the pre-modified dolomite powder, and the addition amount of the octylphenol polyoxyethylene ether is 1%-3% of the mass of the pre-modified dolomite powder; Step 3: Weigh 100 parts of modified dolomite powder, 30-50 parts of nickel slag, 10-25 parts of metakaolin, 5-10 parts of desulfurization ash, and 0.5-1.5 parts of grinding aid, mix well, and grind to a specific surface area of ​​600-750m 2 / kg to obtain composite mineral admixture.

[0006] In the above technical scheme, the present application first blends dolomite powder with gypsum and calcium hydroxide in step 1, and performs preliminary modification under high temperature conditions, thereby promoting the chemical reaction between dolomite powder, gypsum and calcium hydroxide, effectively improving the initial activity of dolomite powder, and laying a good foundation for subsequent surface modification; next, the present application further significantly improves the surface properties of dolomite powder particles, further enhances the dispersibility between dolomite powder particles, and further improves the surface properties of dolomite powder particles by selecting two specific surfactants, hexadecyl trimethyl ammonium chloride and octylphenol polyoxyethylene ether, in step 2. The compatibility and activity of dolomite powder in cement-based materials are improved; further, in step 3, the present application mixes the modified dolomite powder with nickel slag, metakaolin, desulfurized ash and an appropriate amount of grinding aids. By matching the modified dolomite powder with specific mineral admixtures such as nickel slag, metakaolin and desulfurized ash, complementary advantages can be formed, making the hydration products in the concrete more compact, and cooperating with cement to form more hydrated calcium silicate and other gelling substances, better filling the tiny pores inside the concrete, reducing the pores and cracks inside the concrete, and improving the density and strength of the concrete. More hydrated calcium silicate and other gelling substances are formed, and these gelling substances can fill the tiny pores inside the concrete and improve the density of the concrete.

[0007] Preferably, step 1 is specifically as follows: weigh 100 parts of dolomite powder, 20-30 parts of gypsum, and 10-15 parts of calcium hydroxide, mix them evenly, add water at 60-80°C with stirring at 300-500rpm, heat to 120-150°C after adding water, stir for 20-30min, then dry at 500-600°C, and grind to a specific surface area of ​​400-500m 2 / kg, to obtain pre-modified dolomite powder.

[0008] In the above technical scheme, the present application promotes the uniform distribution and sufficient contact of the reactants by controlling the reaction conditions, especially by controlling the reaction temperature and stirring speed, ensuring that the dolomite powder, gypsum and calcium hydroxide can be fully mixed and the expected chemical reaction occurs, thereby further enhancing the activity of the pre-modified dolomite powder.

[0009] Preferably, step 2 is specifically as follows: prepare 20-30 parts of an aqueous solution containing hexadecyltrimethylammonium chloride and octylphenol polyoxyethylene ether, take 100 parts of pre-modified dolomite powder, spray the aqueous solution and stir at 25-30°C and 500-800rpm, continue stirring for 10-20 minutes after adding, and then dry at 100-120°C to obtain modified dolomite powder.

[0010] In the above technical scheme, the present application ensures that the surfactant can be evenly attached to the surface of the dolomite powder particles by controlling the temperature, stirring speed and drying conditions when spraying the aqueous solution, thereby effectively improving the dispersibility between the dolomite powder particles, and promoting the uniform distribution of dolomite powder in cement-based materials, and enhancing the chemical reaction between dolomite powder and cement, thereby increasing the activity contribution of dolomite powder in concrete and further improving the overall performance of concrete.

[0011] Preferably, the grinding aid in step 3 is at least one of triethanolamine, calcium stearate and sodium hexametaphosphate.

[0012] In the above technical solution, the present application adds a grinding aid during the grinding process, which helps to reduce the friction and resistance between particles, improve the grinding efficiency, and maintain the integrity of the particles, avoiding the agglomeration of particles caused by excessive refinement. In addition, the grinding aid can also play a lubricating role during the grinding process, further improving the dispersibility of the particles, so that the final composite mineral admixture has a more uniform particle size distribution and a higher specific surface area, thereby enhancing its activity performance in concrete.

[0013] In the second aspect, the present application provides a composite mineral admixture adopting the following technical solution: A composite mineral admixture is prepared by the preparation method of the composite mineral admixture as described in the first aspect.

[0014] In the above technical scheme, a composite mineral admixture provided by the present application is prepared by the preparation method of the composite mineral admixture provided by the first aspect, and has the characteristics of high activity, good compatibility, and significant synergistic effect. The modified dolomite powder in the composite mineral admixture of the present application cooperates with nickel slag, metakaolin, and desulfurization ash to form a denser and more stable hydration product network in concrete, significantly improving the strength, durability, and working performance of the concrete.

[0015] In the third aspect, the present application provides a concrete adopting the following technical solution: A concrete comprises the composite mineral admixture described in the second aspect.

[0016] Preferably, the concrete comprises the following components in parts by mass: 280-340 parts of cement, 135-170 parts of composite mineral admixture, 690-842 parts of sand, 955-1161 parts of stone, 140-165 parts of water, and 0.94-1.16 parts of admixture.

[0017] In the above technical solution, the present application provides a concrete using the above composite mineral admixture. Due to the addition of the composite mineral admixture, the internal structure of the concrete is more compact, the porosity and the number of cracks are significantly reduced, thereby improving the density, strength and durability of the concrete.

[0018] Preferably, the sand is compounded from machine-made sand and nickel slag in a mass ratio of (6-7):(3-4).

[0019] Preferably, the fineness modulus of the machine-made sand and nickel slag is 3.2.

[0020] In the above technical scheme, the present application further improves the comprehensive performance of concrete by introducing nickel slag as sand in concrete. Nickel slag, as an industrial waste, contains rich active ingredients such as silicon and aluminum. After compounding with machine-made sand, it not only realizes the resource utilization of waste, but also significantly improves the particle grading and activity of sand. The hard particles of machine-made sand provide good skeleton support for concrete, while the active ingredients of nickel slag play a positive role in the cement hydration process, interacting with the composite mineral admixture of the present application, enhancing the bonding force between sand and cement paste, and further promoting the generation of hydration products and the densification of the structure.

[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application modifies dolomite powder and introduces a variety of mineral admixtures to obtain a composite mineral admixture that can significantly improve the comprehensive performance of concrete. The surface properties of the modified dolomite powder have been significantly improved, the dispersibility between particles has been enhanced, and the compatibility and activity with cement-based materials have also been significantly improved. Furthermore, the present application achieves complementary advantages of a variety of mineral admixtures by mixing modified dolomite powder with nickel slag, metakaolin, and desulfurized ash, and can form a more dense and stable hydration product network in concrete, significantly improving the strength and durability of concrete.

[0022] 2. This application not only realizes the resource utilization of industrial waste by introducing nickel slag in the process of concrete preparation, but also further improves the particle grading and activity of concrete through the compounding of the active ingredients inside it with machine-made sand, enhances the bonding force between sand and cement paste, and enhances the density and strength of concrete. DETAILED DESCRIPTION

[0023] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0024] Example 1 A method for preparing a composite mineral admixture comprises the following steps: Step 1: Weigh 100kg dolomite powder, 20kg gypsum, and 10kg calcium hydroxide, mix them evenly, add water at 60℃ and 300rpm, heat to 120℃ and stir for 30min, then dry at 50℃ and grind to a specific surface area of ​​400-500m 2 / kg, to obtain pre-modified dolomite powder.

[0025] Step 2: Take 100 kg of pre-modified dolomite powder, spray 20 kg of aqueous solution at 25 ° C and 500 rpm and stir, continue stirring for 20 minutes after addition, and then dry at 120 ° C to obtain modified dolomite powder.

[0026] The aqueous solution is prepared by dissolving 1 kg of hexadecyltrimethylammonium chloride (CAS No.: 112-02-7) and 1 kg of octylphenol polyoxyethylene ether (emulsifier OP-4) in 18 kg of water.

[0027] Step 3: Weigh 100kg modified dolomite powder, 30kg nickel slag, 10kg metakaolin, 5kg desulfurization ash, and 0.5kg triethanolamine, mix well, and grind to a specific surface area of ​​600-750m 2 / kg to obtain composite mineral admixture.

[0028] Among them, dolomite powder comes from Lingshou County Yongshun Mineral Products Processing Plant.

[0029] Among them, gypsum is natural gypsum.

[0030] Among them, the nickel slag comes from Xinhai Technology Co., Ltd. in Linyi City, Shandong Province.

[0031] Among them, kaolin comes from Shijiazhuang Huijin Mineral Products Co., Ltd.

[0032] Among them, the desulfurization ash comes from Lingshou County Yongshun Mineral Products Processing Plant.

[0033] Example 2 A method for preparing a composite mineral admixture, which is different from Example 1, comprises the following steps: Step 1: Weigh 100kg dolomite powder, 30kg gypsum, and 15kg calcium hydroxide, mix them evenly, add water at 80℃ and 500rpm, heat to 150℃ and stir for 20min, then dry at 600℃ and grind to a specific surface area of ​​400-500m 2 / kg, to obtain pre-modified dolomite powder.

[0034] Step 2: Take 100 kg of pre-modified dolomite powder, spray 30 kg of aqueous solution at 30 ° C and 800 rpm and stir, continue stirring for 10 minutes after addition, and then dry at 100 ° C to obtain modified dolomite powder.

[0035] The aqueous solution is prepared by dissolving 2 kg of hexadecyltrimethylammonium chloride and 3 kg of octylphenol polyoxyethylene ether in 25 kg of water.

[0036] Step 3: Weigh 100kg modified dolomite powder, 50kg nickel slag, 25kg metakaolin, 10kg desulfurized ash, and 1.5kg calcium stearate, mix well, and grind to a specific surface area of ​​600-750m 2 / kg to obtain composite mineral admixture.

[0037] Example 3 A method for preparing a composite mineral admixture, which is different from Example 1, comprises the following steps: Step 1: Weigh 100kg dolomite powder, 25kg gypsum, and 12kg calcium hydroxide, mix them evenly, add water at 70℃ and 400rpm, heat to 140℃ and stir for 22min, then dry at 550℃ and grind to a specific surface area of ​​400-500m 2 / kg, to obtain pre-modified dolomite powder.

[0038] Step 2: Take 100 kg of pre-modified dolomite powder, spray 25 kg of aqueous solution at 28 ° C and 600 rpm and stir, continue stirring for 15 minutes after addition, and then dry at 110 ° C to obtain modified dolomite powder.

[0039] The aqueous solution is prepared by dissolving 1.5 kg of hexadecyltrimethylammonium chloride and 2 kg of octylphenol polyoxyethylene ether in 21.5 kg of water.

[0040] Step 3: Weigh 100kg modified dolomite powder, 40kg nickel slag, 15kg metakaolin, 8kg desulfurization ash, and 1kg sodium hexametaphosphate, mix well, and grind to a specific surface area of ​​600-750m 2 / kg to obtain composite mineral admixture.

[0041] Comparative Example 1 A method for preparing a composite mineral admixture, which is different from Example 1 in that an equal amount of gypsum in step 1 is replaced by calcium hydroxide.

[0042] Comparative Example 2 A method for preparing a composite mineral admixture, which is different from Example 1 in that in step 1, an equal amount of calcium hydroxide is replaced by gypsum.

[0043] Comparative Example 3 A method for preparing a composite mineral admixture, which is different from Example 1 in that an equal amount of hexadecyltrimethylammonium chloride in step 2 is replaced by octylphenol polyoxyethylene ether.

[0044] Comparative Example 4 A method for preparing a composite mineral admixture, which is different from Example 1 in that an equal amount of octylphenol polyoxyethylene ether is replaced by hexadecyltrimethylammonium chloride in step 2.

[0045] Comparative Example 5 A method for preparing a composite mineral admixture, which is different from Example 1 in that nickel slag is not added in step 3.

[0046] Comparative Example 6 A method for preparing a composite mineral admixture, which is different from Example 1 in that no kaolin is added in step 3.

[0047] Comparative Example 7 A method for preparing a composite mineral admixture, which is different from Example 1 in that no desulfurization ash is added in step 3.

[0048] Comparative Example 8 A method for preparing a composite mineral admixture, which is different from Example 1 in that step 3 is as follows: 100 kg of modified dolomite powder and 0.5 kg of triethanolamine are ground to a specific surface area of ​​600-750 m 2 / kg to obtain composite mineral admixture.

[0049] Application Example 1 A concrete comprises 280 kg of cement, 135 kg of composite mineral admixture, 690 kg of sand, 955 kg of stone, 140 kg of water and 0.94 kg of water reducing agent.

[0050] Among them, the cement is Everbright’s P·O42.5 cement.

[0051] Among them, the sand is compounded by machine-made sand and nickel slag in a mass ratio of 6:4.

[0052] Among them, the fineness modulus of machine-made sand and nickel slag is 3.2.

[0053] Among them, the stone is 5-25mm continuously graded crushed stone with a crushing value of 5%.

[0054] Among them, the water reducer is a polycarboxylic acid high-performance water reducer produced by Guangzhou Runhong Chemical Co., Ltd.

[0055] Among them, the composite mineral admixture is prepared by Example 1.

[0056] Application Example 2 A concrete, which is different from Application Example 1, includes 340 kg of cement, 170 kg of composite mineral admixture, 842 kg of sand, 1161 kg of stone, 165 kg of water, and 1.16 kg of water reducing agent.

[0057] Among them, the sand is a compound of machine-made sand and nickel slag in a mass ratio of 7:3.

[0058] Among them, the composite mineral admixture is prepared by Example 2.

[0059] Application Example 3 A concrete, which is different from Application Example 1, includes 310 kg of cement, 155 kg of composite mineral admixture, 767 kg of sand, 1058 kg of stone, 155 kg of water, and 1.05 kg of water reducing agent.

[0060] Among them, the sand is compounded by machine-made sand and nickel slag in a mass ratio of 6.5:3.5.

[0061] Among them, the composite mineral admixture is prepared by Example 3.

[0062] Application Example 4 A concrete, different from that in Application Example 1, in that the sand is manufactured sand.

[0063] Comparative application example 1 A concrete, which is different from Application Example 1 in that the composite mineral admixture is prepared by Comparative Example 1.

[0064] Comparative Application Example 2 A concrete, which is different from Application Example 1 in that the composite mineral admixture is prepared by Comparative Example 2.

[0065] Comparative Application Example 3 A concrete, which is different from Application Example 1 in that the composite mineral admixture is prepared by Comparative Example 3.

[0066] Comparative Application Example 4 A concrete, which is different from Application Example 1 in that the composite mineral admixture is prepared by Comparative Example 4.

[0067] Comparative Application Example 5 A concrete, which is different from Application Example 1 in that the composite mineral admixture is prepared by Comparative Example 5.

[0068] Comparative Application Example 6 A concrete, which is different from Application Example 1 in that the composite mineral admixture is prepared by Comparative Example 6.

[0069] Comparative Application Example 7 A concrete, which is different from Application Example 1 in that the composite mineral admixture is prepared by Comparative Example 7.

[0070] Comparative Application Example 8 A concrete, which is different from Application Example 1 in that the composite mineral admixture is prepared by Comparative Example 8.

[0071] Performance Testing Test items: Concrete of the above-mentioned application examples and comparative application examples.

[0072] Compressive strength: Tested in accordance with GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete".

[0073] Shrinkage deformation, water seepage height, chloride ion permeability coefficient: Tested in accordance with GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete". The water seepage height test adopts the penetration height method, and the test conditions are a water pressure of 1.8MPa and a constant pressure of 24h; the chloride ion penetration test adopts the RCM method.

[0074] The above test results are shown in Table 1.

[0075] Table 1: Combining the data analysis of Application Example 1-4 and Comparative Application Example 1-8, it can be seen that the concrete of Application Example 1-4 performs well in terms of compressive strength, shrinkage deformation, water seepage height and chloride ion permeability coefficient. It can be seen that the composite mineral admixture used in Application Example 1-4 can greatly improve the strength and durability of concrete.

[0076] Specifically, the difference between Application Example 1 and Comparative Application Examples 1-4 is that Application Example 1 uses the composite mineral admixture of Example 1, and the composite mineral admixture of Example 1 is first modified with gypsum and calcium hydroxide, and then further modified with hexadecyltrimethylammonium chloride and octylphenol polyoxyethylene ether compared to Application Examples 1-4. Application Example 1 performs well in terms of performance indicators such as compressive strength, shrinkage deformation, water seepage height and chloride ion permeability coefficient. It can be seen that the modified dolomite powder of the present application can effectively improve the physical and mechanical properties and durability of concrete.

[0077] Further analysis of the data of Application Example 1 and Comparative Application Examples 5-8 shows that the mineral admixtures used in Comparative Application Examples 5-7 did not contain nickel slag, kaolin, or desulfurization ash, and Comparative Application Example 8 only used modified dolomite powder. It can be seen that Application Example 1 performed well in terms of compressive strength, shrinkage deformation, water seepage height, and chloride ion permeability coefficient. This shows the important role of nickel slag, kaolin, and desulfurization ash in composite mineral admixtures. Compounding nickel slag, kaolin, and desulfurization ash on the basis of modified dolomite powder is of great help in improving the performance of concrete, and can significantly improve the physical and mechanical properties and durability of concrete.

[0078] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a composite mineral admixture, characterized in that: The following steps are involved: Step 1: Weigh 100 parts of dolomite powder, 20-30 parts of gypsum, and 10-15 parts of calcium hydroxide, mix them evenly, add 50-60 parts of water while stirring, dry after the reaction is completed, and grind to a specific surface area of ​​400-500m 2 / kg, and pre-modified dolomite powder was obtained; Step 2: Take pre-modified dolomite powder, spray the aqueous solution containing hexadecyl trimethyl ammonium chloride and octylphenol polyoxyethylene ether while stirring, mix evenly and dry to obtain modified dolomite powder, wherein the amount of hexadecyl trimethyl ammonium chloride added is 1%-2% of the mass of the pre-modified dolomite powder, and the amount of octylphenol polyoxyethylene ether added is 1%-3% of the mass of the pre-modified dolomite powder; Step 3: Weigh 100 parts of modified dolomite powder, 30-50 parts of nickel slag, 10-25 parts of metakaolin, 5-10 parts of desulfurized ash, and 0.5-1.5 parts of grinding aid, mix well, and grind to a specific surface area of ​​600-750m 2 / kg to obtain composite mineral admixture.

2. The method for preparing a composite mineral admixture according to claim 1, characterized in that: The step 1 is specifically as follows: weigh 100 parts of dolomite powder, 20-30 parts of gypsum, and 10-15 parts of calcium hydroxide, mix them evenly, add water at 60-80°C with stirring at 300-500rpm, heat to 120-150°C and stir for 20-30min after adding water, then dry at 500-600°C, and grind to a specific surface area of ​​400-500m² / kg to obtain pre-modified dolomite powder.

3. The method for preparing a composite mineral admixture according to claim 1, characterized in that: The step 2 is specifically as follows: prepare 20-30 parts of an aqueous solution containing hexadecyltrimethylammonium chloride and octylphenol polyoxyethylene ether, take 100 parts of pre-modified dolomite powder, spray the aqueous solution and stir at 25-30°C and 500-800rpm, continue stirring for 10-20 minutes after adding, and then dry at 100-120°C to obtain modified dolomite powder.

4. The method for preparing a composite mineral admixture according to claim 1, characterized in that: The grinding aid in step 3 is at least one of triethanolamine, calcium stearate and sodium hexametaphosphate.

5. A composite mineral admixture, characterized in that: The composite mineral admixture is prepared by the preparation method of the composite mineral admixture as described in any one of claims 1 to 4.

6. A concrete, characterized in that: Including the composite mineral admixture as described in claim 5.

7. A concrete according to claim 6, characterized in that: The composition comprises the following components in parts by mass: 280-340 parts of cement, 135-170 parts of composite mineral admixture, 690-842 parts of sand, 955-1161 parts of stone, 140-165 parts of water and 0.94-1.16 parts of admixture.

8. The concrete according to claim 7, characterized in that: The sand is prepared by mixing machine-made sand and nickel slag in a mass ratio of (6-7): (3-4).

Citation Information

Patent Citations

  • Modification method for fluorgypsum

    CN104176955A

  • Modified dolomite powder based mineral admixture and preparation method thereof

    CN106747090A

  • Heat-insulating plastering gypsum for building interior wall and preparation method thereof

    CN108373309A

  • Mineral admixture containing low-silicon dolomite powder and preparation method thereof

    CN116425442A

  • Chemicals to treat wastewater, method for preparing the same and use thereof

    KR101279445B1

Cited By

  • Laterite-nickel ore leaching residue treatment process

    CN120818699A

  • A process for treating laterite nickel ore leach residue

    CN120818699B